2022
DOI: 10.29103/aa.v9i1.6992
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Spirulina platensis as a bioremediator candidate for vaname shrimp (Litopenaeus vannamei) wastewater

Abstract: The purpose of this study was to determine the effectiveness of Spirulina platensis for remediation of vannamei shrimp culture waste. The method used in this study was a Non-Factoral Completely Randomized Design (CRD) with 4 treatments and 3 replications, namely (A) Control; (B) 50% waste (1500 ml waste + 1500 ml water) + technical fertilizer + Spirulina inoculant; (C) 75% waste (2,250 ml of waste + 750 ml of water) technical fertilizer + Spirulina inoculant; (D) 100% waste + technical fertilizer + Spirulina i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Meanwhile, increment of medium pH would extend the lag phase of A. platensis (Putri 2019). Furthermore, Arthrospira platensis cultured in vannamei culture waste water showed the exponential phase in day 3 rd to day 6 th of cultivation, while the stationary phase was on day 7 th and the declining phase was on day 8 th (Hartami et al 2022). Generally, peak value of Arthrospira platensis's biomass is started on day 3 rd of cultivation which consider in the exponential phase.…”
Section: Discussionmentioning
confidence: 93%
“…Meanwhile, increment of medium pH would extend the lag phase of A. platensis (Putri 2019). Furthermore, Arthrospira platensis cultured in vannamei culture waste water showed the exponential phase in day 3 rd to day 6 th of cultivation, while the stationary phase was on day 7 th and the declining phase was on day 8 th (Hartami et al 2022). Generally, peak value of Arthrospira platensis's biomass is started on day 3 rd of cultivation which consider in the exponential phase.…”
Section: Discussionmentioning
confidence: 93%
“…Arthrospira platensis cells entered the log or exponential phase on the third to the 6th day of culture. This is following the research of Hartami et al, (2022). According to Mauretsa et al (2019), sufficient nutrients can facilitate Arthrospira platensis in breeding to achieve maximum growth.…”
Section: Cell Growthmentioning
confidence: 91%
“…The highest growth of Arthrospira platensis cells was obtained on the seventh day of culture. Arthrospira platensis cells in the study of Hartami et al, (2022) underwent a stationary phase on the seventh day, marked by the density of Arthrospira platensis reaching the peak population. Arthrospira platensis cell growth decreases or cells die when the nutrients in the culture media are insufficient for cell growth (Mauretsa et al, 2019).…”
Section: Cell Growthmentioning
confidence: 96%
“…Based on reference [5], waste solid of vannamei shrimp culture contains 1.92% of organic carbon (C), 0.54% of total nitrogen, and 1.7% of phosphate. Utilization of vannamei shrimp culture wastewater had been done [6] to cultivate Spirulina sp. The result showed that vannamei shrimp culture wastewater could increase density and growth of Spirulina sp.…”
Section: Introductionmentioning
confidence: 99%